Assessing the performance of the existing and proposed network of marine protected areas to conserve marine biodiversity in Chile - Tognelli, Marcelo Fabio (2009)
The growing concern about the profound influence of human activities on marine ecosystems has been the driving force behind the creation of marine reserves in the last few decades. With almost 4200 km of coastline, Chile has not been the exception to this trend. A set of conservation priority sites has recently been proposed by the Chilean government to expand the current marine reserve network. In this study, we used the most comprehensive information currently available on the distribution of 2513 marine species in Chile to assess the efficiency of the existing system of marine protected areas (MPA) and the conservation priority sites identified by the government. Additionally, we evaluated the vulnerability of the reserve network selected with respect to threatening human activities. Our results show that both the existing protected areas and the proposed priority sites are relatively effective at protecting Chilean marine biodiversity. However, the majority of the species that are not represented within the existing or projected MPA network have very restricted distributions and are, therefore, of high conservation concern. To cover all species requires a network of 35 MPAs (46% of the total number of planning units). Many of the sites identified as irreplaceable present conflict with one or more human activities, particularly in the central region of the country. This study emphasizes the need for a systematic conservation planning approach to maximize the representation of species and prioritize those areas where conflicts between marine biodiversity conservation and human activities may occur.